EKOENZIM DARI BERBAGAI JENIS KULIT JERUK - Azmah Nururrahmani; M. Rio Hibatulloh; Revani Ayu Nabila; Kusnadi; Peristiwati Djuarsa (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2023)
Most of the existing waste is organic waste originating from household activities. To overcome vegetable and fruit waste, fermentation is conducted by adding brown sugar and water to produce ecoenzymes. Ecoenzymes have many uses, from cleaning agents, and insecticides, to natural fertilizers. Ecoenzymes from various types of organic waste can provide different characteristics. The research method was an experimental laboratory to determine the differences in the peel type of medan oranges (Citrus x sinensis), squeezed oranges (Citrus reticulata), and lemons (Citrus limon) on the organoleptic character of eco enzymes and pH values. Through this research, it is notable that the eco enzymes from Citrus x sinensis peels have good eco enzyme criteria and the pH value of all orange peels has a pH of 3.